Detection of CAF-1/p60 in peripheral blood as a potential biomarker of HNSCC tumors. (September 2021) - Merolla, Francesco; Ilardi, Gennaro; Di Spigna, Gaetano; Russo, Daniela; Martino, Francesco; Varricchio, Silvia; Dell'Aversana, Giovanni Orabona; Mascolo, Massimo; Covelli, Bianca; Caltabiano, Rosario; Broggi, Giuseppe; Audino, Giovanni; et al.
Abstract: To date, a very small number of serum biomarkers have been identified for clinical use in squamous carcinomas of the head and neck region. Chromatin Assembly Factor-1 (CAF-1) heterotrimeric complex subunit CAF1/p60 expression levels have been reported to be of prognostic value in Oral Squamous Cell Carcinoma (OSCC), as well as in other human solid tumors. Here our aim was to detect and quantify CAF1/p60 in the peripheral blood of Head and Neck Squamous Cell Carcinoma (HNSCC) patients, and to investigate the possible associations between serum concentration of CAF-1/p60 and HNSCC tumors. A total of 63 HNSCC patients (51 OSCC, 8 OPSCC, 3 laryngeal SCC, and 1 rhinopharynx SCC) and 30 healthy controls were enrolled. The serum levels of CAF-1/p60 were measured by ELISA assay before and after surgery. Serum CAF-1/p60 concentration resulted significantly higher in cancer patients, compared with healthy controls, in pre-surgery samples (P < 0.05). Serum levels of CAF-1/p60 significantly decreased in serum samples taken after surgery (P < 0.05). Our results demonstrated that CAF-1/p60 may be detected in serum, suggesting a role for CAF-1/p60 as potential soluble biomarkers in HNSCC tumors.